(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article describes the process of vocational guidance of students in the teacherstudent system to determine the knowledge and skills of students in a particular subject, the results of vocational training in accordance with the requirements, rules, regulations, etc., Basis for the management system. and the study of the mechanism, its accounting and evaluation.